Pengaruh Serbuk Ban Bekas Sebagai Campuran Agregat Halus Pada Campuran Aspal Porous - Martina, Nunung; Hasan, Muhammad Fathur Rouf; Setiawan, Yanuar (Politeknik Negeri Semarang, 2019)
The porous asphalt mixture is a new generation of flexible pavement that is able to pass water in the upper layer (wearing course) both vertically and horizontally. The porous asphalt layer effectively provides more safety, especially when it rains to avoid aquaplaning which causes roughness of the surface to be more rough. Therefore, at this time there are many studies on the use of alternative materials to replace the limited natural materials with materials that can be utilized. The results showed that porous asphalt mixture with used tire crumb as a fine aggregate mixture had an increase in flow value of 6.32% with a decrease in stability value by 27.52% and a decrease Marshall Quotient value at 31.82%. The testing of roughness is increased by 17.71% and Mu-Meter 24.14%. This research is effective in overcoming environmental problems which include processing tire waste of 3.03 tons for 1 km of road pavement construction work.